PERAN KEPUASAN KARIR DAN BUDAYA ORGANISASI TERHADAP KINERJA SDM - Diah Ayu Kusumawati; Mutamimah Mutamimah (Master of Management, Mataram University, 2022)
Research on career satisfaction and organizational culture is very important because employee career satisfaction can improve employee performance which is supported by the organizational culture. The purpose of this study is to determine the optimization performance to career satisfaction moderated by organizational culture on non-medical permanent employees at the Islamic Hospital of Semarang. This study used questionnaire with 191 respondents. The results of this study found three aspects; first, self-competence and job demand have a positive and significant impact on career satisfaction. Second, self-competence and job demand have a positive and significant impact on performance. Third, career satisfaction has a positive and significant impact on performance supported by organizational culture at the Islamic Hospital of Semarang. Keywords: self competence, job demand, Islamic organizational culture, career satisfaction, performance